Pengaruh Kepribadian Efikasi Diri Motivasi Kerja Terhadap Kinerja Pegawai Badan Pusat Statistik Kabupaten Pandeglang - Gugun Gunarto; Hadi Subhan; Dede Engkos; Subarji Subarji (E-Journal Studia Manajemen, 2022)
Research on employee performance has been carried out by academics before, but explanations of employee performance through personality, self-efficacy, and work motivation are rarely done, so the authors fill this gap. This study aims to find factors that can explain the performance of employees at BPS Pandeglang Regency. The analysis was conducted by examining the influence of personality, self-efficacy, and work motivation on employee performance. The research approach uses a quantitative survey from a total population of fifty-two people, selected based on using the slovin formula as many as forty-two people/sample from BPS employees of Pandeglang Regency. An interesting finding from this study is the partial and simultaneous effect of the predictor variables. By paying attention to the R Square value of zero point six hundred forty-six, this shows that simultaneously the influence of personality, self-efficacy, and work motivation on employee performance is sixty-four point six percent, while the rest is influenced by other factors outside the research model. this. These results give the conclusion that simultaneously and partially, personality variables, self-efficacy, and work motivation can be used as predictor variables for employee performance. The implications and suggestions of these findings are discussed for the benefit ofacademics and human resource management practitioners.